Development of Potent and Selective Inhibitors for Group VIA Calcium-Independent Phospholipase A(2) Guided by Molecular Dynamics and Structure-Activity Relationships - Mouchlis, Varnavas D. (J Med Chem, 2016)
The development of inhibitors for phospholipases A(2) (PLA(2)s) is important in elucidating their implication in various biological pathways. PLA(2) enzymes are an important pharmacological target implicated in various inflammatory diseases. Computational chemistry, organic synthesis and in vitro assays were employed to develop potent and selective inhibitors for Group VIA calcium-independent PLA(2). A set of fluoroketone inhibitors, were studied for their binding mode with two human cytosolic PLA(2) enzymes: Group IVA cPLA(2) and Group VIA iPLA(2). New compounds were synthesized and tested against three major PLA(2) enzyme. This study led to the development of four potent and selective thioether fluoroketone inhibitors as well as a thioether keto-1,2,4-oxadiazole inhibitor for GVIA iPLA(2), which will serve as lead compounds for future development and studies. The keto-1,2,4-oxadiazole functionality with a thioether is a novel structure and it will be used as a lead to develop inhibitors with higher potency and selectivity towards GVIA iPLA(2).